Les Tendances Womanistes Dans Les Oeuvres Des Romancieres De L'afrique Francophone - Bestman, Rukayat Folajoke (2015)
The study examined the position of black women in relation to feminist theory, identified and discussed the varieties of womanism as an African version of feminism. It also analysed Francophone African women's novels from the womanist perspective. This was done with a view to exploring the thematic of Francophone African women's novelistic works.